2013
DOI: 10.1074/mcp.o112.024372
|View full text |Cite
|
Sign up to set email alerts
|

The DegraBase: A Database of Proteolysis in Healthy and Apoptotic Human Cells

Abstract: Proteolysis is a critical post-translational modification for regulation of cellular processes. Our lab has previously developed a technique for specifically labeling unmodified protein N termini, the ␣-aminome, using the engineered enzyme, subtiligase. Here we present a database, called the DegraBase (http://wellslab.ucsf.edu/degrabase/), which compiles 8090 unique N termini from 3206 proteins directly identified in subtiligase-based positive enrichment mass spectrometry experiments in healthy and apoptotic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
179
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(197 citation statements)
references
References 47 publications
17
179
1
Order By: Relevance
“…Although earlier studies have identified Ͼ1000 putative caspase substrates in nonneuronal cells (20,21), the identification of neuronal caspase-3 substrates, and their possible involvement in LTD, had yet to be established. To our knowledge, ours is the first systematic study of caspase-3 substrates in neurons.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although earlier studies have identified Ͼ1000 putative caspase substrates in nonneuronal cells (20,21), the identification of neuronal caspase-3 substrates, and their possible involvement in LTD, had yet to be established. To our knowledge, ours is the first systematic study of caspase-3 substrates in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 56 proteins, 19 (18 human orthologs) are reported on the CAspase Substrate dataBAse Homepage (CASBAH, http:// bioinf.gen.tcd.ie/casbah/), and 43 are also in the recently established DegraBase (http://wellslab.ucsf.edu/degrabase/ index.htm) derived from human samples analyzed with the same methods used in this study (20,21). We analyzed the P4 to P1Ј motif composition of putative caspase-3 substrates identified from STS treated neurons.…”
Section: Identification Of Caspase-3 Substrates In Neurons-mentioning
confidence: 99%
See 3 more Smart Citations